The World Defense Expenditure 2019 and trends in the Covid19 era - Zanidis, Themistoklis (HAPSc Policy Briefs Series, 2020)
This paper focuses on the recent publication of the SIPRI Institute on global defense spending for 2019. The latter is on the rise for 5th consecutive year, climbing to the highest point since 1988, the Cold War era. This fact has multiple interpretations. The most important construe apropos the geopolitical competition, from hegemonic competition between the United States and China to regional ones, can constitute perils to international security with unpredictable and catastrophic consequences for global peace, economy and trade. The recent crisis over the Covid-19 pandemic has expanded the breach between the West and China, raising skepticism or even suspicious on both sides. Relations between the two powers, the United States and China, have deteriorated, threatening global stability while states are unable to find a commonplace for a successful and definitive fight against the pandemic. The unstable geopolitical environment has experienced the burden of the pandemic crisis due to Covid-19. The restrictive measures taken by governments to intercept the pandemic may be the reasoning for restraining defense spending world widely. This prospect can be a future reality if we take into account the cost caused to national and global economy by the protracted lockdown. Therefore, governments may be compelled to increase spending on the welfare state (health infrastructure, support for the lower classes, support for sectors of the economy most affected by the pandemic such as transportation and tourism) by cutting the defense budget. The latter consists a critical indicator of national sovereignty and its fully understandable the fact that is exceptionally difficult for states to make unforced military budget cuts. However, because of the recent extremely critical situations experienced by humanity as a whole, governments should consider limiting their defense spending, which will be monitored closely by the United Nations for a limited time and focus on dealing with the economic and social effects of the lockdown.